A roadmap to precision medicine for multiple sclerosis - Chitnis, Tanuja; Prat, Alexandre (Multiple sclerosis, 2020)
Multiple sclerosis (MS) affects approximately 1 million persons in the United States, and is the leading cause of neurological disability in young adults. The concept of precision medicine is now being applied to MS and has the promise of improved care. MS patients experience a variety of neurological symptoms, and disease severity ranges from mild to severe, and the biological underpinnings of these phenotypes are now starting to be elucidated. Precision medicine involves the classification of disease subtypes based on the underlying biology, rather than clinical phenotypes alone, and may govern disease course and treatment response. Over 18 disease-modifying drugs have been approved for the treatment of MS, and several biomarkers of treatment response are emerging. This article provides an overview of the concepts of precision medicine and emerging biological markers and their evolving role in decision-making in MS management.